Estudo da ampliação da escala na produção de néctar de Bacuri (Platonia insignis Martius) com aplicação de preparações enzimáticas comerciais - Aquino, Andréa Cardoso de (2012)
The regional fruit market has been gaining space in Brazil, both for the search of alternatives by producers and for the search of new options of fruits by consumers. Among high priority fruits for studies and incentives we can highlight bacuri (Platonia insignis Mart.), for its economical importance in North and Mid-North regions in Brazil. However, the high consistency of the bacuri pulp caused by the high polysaccharide amount (pectin, hemicellulose, cellulose and lignin) in fabrics make the spread of its nectar impossible. This allied to the unawareness of the parameters involved in the processing of bacuri nectar that makes the production scale enlargement difficult. The maceration of the bacuri pulp, by means of the application of enzymes with pectinolytic, hemicellulolytic and cellulolytic activities, enables the reduction in the pulp consistency making the preparation of bacuri nectar possible within the standards required by the Ministry of Agriculture and Food Supply, through the Normative Instruction No. 12, of September 4th, 2003 (minimum 20% of pulp). Thus, the general purpose of this study is to evaluate the enzymatic maceration process of the bacuri pulp so as to obtain the nectar proper for commercialization, as well as studying the production scale enlargement of this nectar. The study began with the chemical and physical-chemical characterization, composition of volatile compounds, cytochemical structure and rheological behavior of integral bacuri pulp. Then, the consistency reduction in the bacuri pulp was evaluated through the enzymatic maceration study. In this step, we studied the application of commercial enzymatic preparations Pectinex Smash XXL, Shearzyme 500 L, Pectinex Ultra SP-L, Viscozyme L and Celluclast in the bacuri pulp, as well as the parameters influence such as incubation temperature (20 to 35 °C), duration of incubation (60 to 180 min), concentration of the enzymatic preparations (53 to 267 µL.100gpulp -1 ) and combinations of the enzymatic preparations (Pectinex XXL and Celluclast; Viscozyme L and Celluclast) in the maceration efficiency. In the next step, we identified the chemical, physical-chemical, cytochemical, chromatographical and rheological changes occurred in the bacuri pulp submitted to enzymatic maceration. Then, the influence study of the sensorial profile was started and the acceptability of the bacuri nectar was prepared with enzymatically macerated pulp. For this step, nectars with different pulp concentrations were prepared (10 and 20%); these macerated pulps in different conditions. Finally, the production scale enlargement of the bacuri nectar and the optimization of pasteurization (80 to 120 °C) in tubular pasteurizer were evaluated, through factors that direct or indirectly 4 influence on the nectar quality. The results of the physical-chemical and cytochemical analyses evidenced high consistency of the bacuri pulp due to considerable amounts of pectin, hemicellulose, cellulose and lignin. 34 volatile compounds, being 15 terpenes, characterizing as the main class of volatile compounds identified in the integral bacuri pulp. The rheological behavior of the integral bacuri pulp was characterized as nonNewtonian pseudoplastic. The application of the combination of 40 µL.100gpulp -1 of Pectinex XXL and 100 µL.100gpulp -1 of Celluclast reached appropriate enzymatic maceration in the bacuri pulp, by reducing its consistency in approximately 80.12%. The chromatography results showed that during the enzymatic maceration of the bacuri pulp there was an increase in the volatile compound number. As for the rheological analyses, the oscillatory trials showed that the bacuri pulp macerated in two different conditions (application of 40 µL.100gpulp -1 of Pectinex XXL and application of 100 µL.100gpulp -1 of Celluclast; 40 µL.100gpulp -1 of Viscozyme L and 100 µL.100gpulp -1 of Celluclast) reduced in the viscoelasticity of the bacuri pulp. The outflow curve showed pseudoplastic non-Newtonian behavior of the bacuri pulp enzymatically macerated. By means of sensorial analyses, we were able to observe that the bacuri pulp macerated in two different conditions (application of 40 µL.100gpulp -1 of Pectinex XXL and 100 µL.100gpulp -1 of Celluclast and application of 40 µL.100gpulp -1 of Viscozyme L and 100 µL.100gpulp -1 of Celluclast) managed to formulate a nectar within the standards required by the Brazilian Legislation, with good acceptance and good intention of purchase. The bacuri nectar with 20% of pulp, prepared in pilot scale, in the 1:2 conditions of pulp and water, enzymatic maceration with application of 40 µL.100gpulp -1 of Pectinex XXL and 100 µL.100gpulp -1 of Celluclast, incubation in agitation reactor, 80 minutes of incubation, incubation temperature of 30 °C, 200 rpm agitation, pasteurization at 80 °C during 15 seconds in tubular pasteurizer and aseptic bottling in hood, managed to obtain microbiological safety without affecting its acceptance and noticeable sensorial characteristics to consumer's taste, beyond it does not show darkening.